The Challenges and Strategies in Writing Descriptive Text on Local Places in the EFL Essay Writing Course - M. Akram Mulyasin; Ahmad Zamzam; Lalu Jaswadi Putera; Muhammad Amin; Hajriana Arfah (Universitas Majalengka, 2023)
The objectives of this study were to explore the challenges faced by students in writing descriptive text about local places and to describe how they deal with these challenges. A descriptive method was used, with a writing test and a questionnaire as instruments. From the results of the writing test, the students' scores on the organization aspect were the lowest, which means that students still have difficulties structuring their writing effectively and presenting their ideas in a clear and logical way. It involves issues like paragraph structure, coherence, and transitions between paragraphs. In addition, from the students' responses in the questionnaire, it was found that more than half of the students who participated in the questionnaire section felt that limited vocabulary was their main challenge in writing descriptive texts about local places. This indicates that the students felt that they did not have enough choice of words or phrases to effectively describe the place they were writing about. Moreover, to deal with the challenges, they used various strategies to navigate the complexity of writing about local places. These strategies include thorough observation, pre-writing, revision before completion, seeking examples, seeking feedback from peers, utilizing the power of artificial intelligence (AI), utilizing visual references, and regular practice. In conclusion, the paper shows the challenges students faced in writing descriptive text about local places and the strategies they employed to address these challenges.